Amino-acid amendment of Arginine-325-Tryptophan in rs13266634 genetic polymorphism studies of the SLC30A8 gene with type 2 diabetes-mellitus patients featuring a positive family history in the Saudi population - Alharbi, Khalid Khalaf; Abudawood, Manal; Ali Khan, Imran (Journal of King Saud University. Science, 2021)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder with chronic hyperglycemia. Genome-wide association studies (GWAS) have identified many genes and, among them, solute carrier family 30 member 8 (SLC30A8) was one of the important genes linked to the development of T2DM risk. The relationship between T2DM and the SLC30A8 gene is linked through zinc, which plays a key role in the storage and secretion of insulin. The rs13266634 polymorphism includes a strong genetic association in case-control and meta-analysis studies of the global population. The aim of this current study was to scrutinize the genetic relationship between the rs13266634 polymorphism in the SLC30A8 gene with T2DM subjects selected with a family history in the Saudi population. This study involved 120 cases of diagnosed T2DM and 120 confirmed healthy controls that were recruited to screen rs13266634 polymorphisms through a genotyping analysis followed by PCR and RFLP analysis. Baseline characteristics between cases and controls have been evaluated with Student’s t-test. The study results confirmed the genetic association between the allele (p = 0.001), genotypes (CT = 0.005 and TT = 0.03), and various genetic patterns of inheritance (p = 0.001 and p = 0.02). Both analysis of variance (ANOVA) and binary logistic regression analysis revealed non-signiifcant association with T2DM cases and biochemical parameters (p > 0.05). In conclusion, the current results have confirmed the strong genetic association between T2DM cases and controls in the Saudi population with rs13266634 polymorphisms of the SLC30A8 gene.